PENGEMBANGAN ALAT PERAGA PANEL SURYA SEBAGAI MEDIA PEMBELAJARAN DI SMA TARAKANITA GADING SERPONG - Darmawan, Marten; Gunawan, Harjadi; Pranawa, Kertarta; Mustika, Donny; Soewono, Arka (Jurnal Abdimas Bina Bangsa, 2024)
Tarakanita Gading Serpong Senior High School aims to be an educational institution as well as a research center that adheres to the concept of education for sustainable development. Therefore, the staff of Tarakanita Gading Serpong High School wanted a teaching module that could serve as a learning tool for students, as well as a research instrument for the staff to study the use of renewable energy sources in the form of solar power. To meet their needs, a prototype of a small solar module that can simulate how a solar panel works and measure its output voltage, current, and electrical power was designed and built. The module is equipped with a 50 Wp polycrystalline solar panel, a solar charge controller to regulate the distribution of electric current, an 18 Ah battery to store energy, and an electrical load in the form of an 18-Watt light bulb.  The solar module is designed to be easily moved and operated indoors or outdoors. When the module is indoors, a 75 W Halogen UV lamp is used as a proxy for sunlight. Hopefully, this solar module can serve as an effective learning medium to introduce the use of solar power as a renewable energy source for Tarakanita Gading Serpong High School students.